#TITLE_ALTERNATIVE# - PURWANTI ( NIM : 22714001 ) ; Tim pembimbing : Irwan Iskandar, S.T., M.T., Ph.D.;Agus M. Ramdh, FITRI
This study aims to clarify non isothermal groundwater flow in geothermal area in the southern flank of Mount Rajabasa and understanding thermal effect to groundwater flow in the area. Sub surface hydrogeological condition of the study area was re-constructed based on, geological mapping, geophysical data and water chemistry data. Based on the reconstruction the study area is comprised by four geological units those are andesite lava, volcanic breccia, tuff and andesite boulder. Geothermal manifestation e.g. hot springs and fumaroles are controlled by fault that was exist in Pangkul Area. Quantitative analysis of non isothermal model groundwater flow was built using SEAWAT MODFLOW 2010.1. Based on hydrochemistry and isotope analysis, on the well pad A fault zone there is hotwater and steam which are product from mixing between meteoric water and thermal fluids (probably with H2S content). The result of isotope data has shown the interaction between lithology and water due thermal flow and nearly approach to meteoric water line. At the well pad A zone meteoric water has been infiltrated only at 400-50m because there is raised convection flow on the fault zone due thermal activity.